Seleção de fungos de decomposição branca para a redução da toxicidade do acefato - JARDIM, Valéria de Lima (2010)
Brazil is one of the top pesticides using countries in the world, being the State of Goiás a potential contributor due to its large production of industrial tomatoes. Among the most widely used pesticides is the organophosphate Acephate with toxicological characteristics capable of infecting both living beings and the environment. There are several seeking solution studies to remediate xenobiotic compounds, being microorganisms an important biotechnological tool against them. The aim of this study was to select rot-white fungal that can produce oxidative enzymes under certain conditions, in the presence of Acephate, evaluating their effectiveness in reducing its toxicity. Thus, the study was divided into three parts: testing on solid medium under different nutritional conditions, tests in liquid culture medium under two different conditions (shaking and static) and development of analytical methodology to evaluate the decrease of Acephate toxicity. We defined two levels of Acephate, 10 and 50%, which were treated by the following species: Trametes versicolor, Trametes villosa, Pycnoporus sanguineus, Phanerochaete chrysosporium and Lentinus edodes. In solid medium all species showed mycelial growth and satisfying development in the presence of Acephate under standard nutritional conditions. The concentration of 50% Acephate caused limitation to Trametes villosa in solid and liquid medium cultivation. The opposite occurred to Pycnoporus sanguineus, which had good results in the development and production of enzymes in the presence of Acephate. Lignin Peroxidase in Phanerochaete chrysosporium was present with a 15.77U.mL-1 only in Acephate 50%, suggesting that the pesticide may induce its enzyme complex. The enzyme Laccase excelled in Pycnoporus sanguineus in the two culture conditions, being the largest peak 45.95 U.mL-1 in 50% Acephate in shaking. However, the best value for the production of Laccase from Trametes villosa was in the static condition: 73.55 U.mL-1 in Acephate 10%. The toxicity tests applied, NRU and Cholinesterase Enzyme Inhibition, proved that in these conditions there was no formation of the metabolite Methamidophos. The toxicological methodology developed to assess the toxicity reduction in the treated supernatant was efficient and promising to monitor and investigate environmental contamination. The samples treated by fungi showed 100% increase of Cholinesterase compared to the control group (no treatment) for T. villosa and 91.7% for P. sanguineus. These results showed that the enzyme complex of the fungi studied is capable to reduce Acephate toxicity, proving that well managed rot-white fungal can bring environmental benefits of mitigation.